Kendala Pelaksanaan Manajemen Hubungan Masyarakat di Sekolah - Yunia Putri Daulay, Ericha; Mahnun , Nunu; Amin, Muhammad (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to determine the obstacles to implementing public relations management in schools. This research uses a case study approach at one of the vocational schools in Riau namely the Riau Tax Vocational High School (SMK). The research informants were the Head of the School, the Deputy Head of Public Relations, and the Head of the Department at the Riau Taxation Vocational School. This study found that the implementation of public relations management at the Riau Tax Vocational School has been running as it should. This was proven by the existence of school partnerships with several existing agencies to make public relations programs successful. In addition, communication has also been good through meetings with parents of students to convey the progress of students both academic and non-academic, meetings with committees to strengthen cooperative relations, and meetings with school partners to coordinate cooperation. Meanwhile, regarding the implementation of public relations on the aspect of the school's image, it was quite good with the facilitation of the development of student's interests and talents in extracurricular activities. Other results found that schools experienced problems in carrying out their activities: 1) Lack of parental participation, 2) Limited school operational funds, and 3) Schools were not ready to face the times for the curriculum synchronization process. This has implications for the smooth implementation of public relations and of course, if the school does not immediately anticipate it will affect the image and quality of the school going forward